The Effect of Giving Sport Massage Treatment on Physical Fitness in Student Activity Units Football Players University of Sand Pengaraian - Deri Putra; Resdianto, Resdianto; Prawibowo, Muhammad; Indah , Debby (Universitas Majalengka, 2025)
Health is a state of physical, mental, spiritual, and social well-being that enables individuals to live productively socially and economically. In the context of sports, physical fitness is an important aspect that supports athlete performance. One method used to improve fitness and prevent injury is through sports massage therapy or sports massage. This therapy plays a role in facilitating circulation blood, accelerate muscle recovery, reduce nerve tension, and improve athlete flexibility and performance. Application of sports massage to Student Activity Unit (UKM) players Pasir Pengaraian University Football aims to improve the physical and mental condition of players, minimize the risk of injury, and restore the best abilities during the match. Thus, sports massage becomes an important intervention in the athlete's training program to achieve optimal performance on the field.